Implementation of the Integrated One Way Data in Improving the Quality of Public Services in Rappang. Issue 1 (March 2021) - Saifullah,; Madaling,; Bibin, Muhammad; Hardianti,
Abstract: AI is a type of computer science, the essence of it is to try to make computers or devices replicate the mechanism of knowledge of human cognition and thought, to think like a human being even exceeded human beings. Governments around the world are currently facing pressure from various parties to improve the quality of public services in providing information to the public. This makes the role of E-Government increasingly important for all decision-makers. This research found there are many influencing factors which become a big challenge in implementing artificial intelligence in government village. Human resources capability becomes a major factor that makes implementing artificial intelligence in the village is not going effective. In addition, the second factor is the limitation of data. It is multiple effects of human resource capability. The low capability makes the management data is not well integrated. The third factor is budget. It is because Village Government has not more budget for the maintenance system.